Optimum battery depth of discharge for off-grid solar PV/battery system - Hlal M.I.; Ramachandaramurthy V.K.; Sarhan A.; Pouryekta A.; Subramaniam U. (Elsevier Ltd, 2023)
Electric load loss; Genetic algorithms; Multiobjective optimization; Optimization; Secondary batteries; Battery systems; Cost of energies; Depth of discharges; Multi-objective optimization models; Non dominated sorting genetic algorithm (NSGA II); NSGA-II; Off-grid system; Solar PV systems; Loss of load probability